Predictors of starting antimicrobial treatment in patients with nontuberculous mycobacterial lung disease in the Italian scenario: A SITA GIOVANI-IRENE promoted web-survey. (April 2021) - Lombardi, Andrea; Colaneri, Marta; Sambo, Margherita; Di Matteo, Angela; Sacchi, Paolo; Fabbiani, Massimiliano; Codecasa, Luigi; Aliberti, Stefano; Blasi, Francesco; Bandera, Alessandra; Bruno, Raffaele; Gori, Andrea
Abstract: The disease burden due to nontuberculous mycobacteria is growing worldwide, consequently to improved diagnostic abilities and an increase in the individuals at risk. Uncertainties exist about the right moment on which start treatment. We investigated the clinical features associated with starting an antimicrobial treatment in patients with nontuberculous mycobacterial lung disease among Italian physicians involved in the field. We found that in real life predictors of starting antimicrobial treatment are quite adherent to international guidelines, with some uncertainties regarding the implication of immunosuppressive drugs. Highlights: Predictors of treatment start for NTM-LD in real life are quite adherent to guideline. Due to rarity physicians rarely encounter this disease in daily practice. Uncertainties exist about the impact of immunosuppressive drugs.